2013
DOI: 10.4049/jimmunol.1203203
|View full text |Cite
|
Sign up to set email alerts
|

Lymphotoxin β Receptor Regulates the Development of CCL21-Expressing Subset of Postnatal Medullary Thymic Epithelial Cells

Abstract: Medullary thymic epithelial cells (mTECs) play a pivotal role in the establishment of self-tolerance in T cells by ectopically expressing various tissue-restricted self-Ags and by chemoattracting developing thymocytes. The nuclear protein Aire expressed by mTECs contributes to the promiscuous expression of self-Ags, whereas CCR7-ligand (CCR7L) chemokines expressed by mTECs are responsible for the attraction of positively selected thymocytes. It is known that lymphotoxin signals from the positively selected thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
111
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 110 publications
(129 citation statements)
references
References 34 publications
5
111
2
Order By: Relevance
“…Presumably this would facilitate more interactions between the proTs and mTECs. This crosstalk provides important stimulatory signals for mTECs, which turn over every 10 to 14 days (47,48), through receptor activator of NF-κB, RANKL, CD80/86, LTβR, and CD40 (26,(49)(50)(51)(52). The difference in effects on short-term and long-term thymopoiesis and TEC recovery seen between differing input populations of proTs would suggest that using a combination of DN2 and DN3 proTs may be an optimum approach.…”
Section: Discussionmentioning
confidence: 99%
“…Presumably this would facilitate more interactions between the proTs and mTECs. This crosstalk provides important stimulatory signals for mTECs, which turn over every 10 to 14 days (47,48), through receptor activator of NF-κB, RANKL, CD80/86, LTβR, and CD40 (26,(49)(50)(51)(52). The difference in effects on short-term and long-term thymopoiesis and TEC recovery seen between differing input populations of proTs would suggest that using a combination of DN2 and DN3 proTs may be an optimum approach.…”
Section: Discussionmentioning
confidence: 99%
“…The initial formation of Aire + mTECs depended on RANK signals, whereas the continued mTEC development to the involucrin + stage was mapped to the activation of lymphotoxin β receptor (LTβR) signals provided by mature thymocytes [25]. Lkhagvasuren et al reported that CCL21-expressing mTECs contained a cell population distinct from Aire-expressing mTECs and that the accumulation of this CCL21 + Aire -mTEC subpopulation occurred late during postnatal ontogeny [26]. It was also noted that the postnatal accumulation of CCL21 + Aire -mTECs was regulated by LTβR signals [26], of which the ligand lymphotoxin was provided by positively selected thymocytes [25].…”
Section: Cortical Thymic Epithelial Cells (Ctecs) and Medullary Thymimentioning
confidence: 99%
“…Ribeiro et al [18] further demonstrate that the combination of RANK and CD40 signals, the ligands of which are produced by positively selected thymocytes [8,10], is important for the development of CCRL1-EGFP low mTECs. Thus, the analysis of CCRL1-EGFP reporter mice suggests a novel heterogeneity in postnatal mTECs.It has been shown that mTECs are heterogeneous in terms of the expression of various molecules, including class II MHC, CD80, Aire, and CCL21 [22][23][24][25][26]. White et al described that Aire expression and terminal differentiation within mTECs are temporally separable events that are controlled by distinct mechanisms.…”
mentioning
confidence: 99%
See 2 more Smart Citations